2018
DOI: 10.1007/s00261-018-1683-0
|View full text |Cite
|
Sign up to set email alerts
|

Reader agreement and accuracy of ultrasound features for hepatic steatosis

Abstract: Large hepatic vein blurring, liver-kidney contrast, and overall impression provided the highest reader agreement. Large hepatic vein blurring may provide the highest classification accuracy for dichotomized grading of hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…This ratio is reported to be useful in diagnosing cases of ≥30% steatosis [14]. The USG criteria were the presence of liver brightness and posterior attenuation, with stronger echoes in the hepatic parenchyma in comparison to the renal parenchyma and vessel blurring [15]. USG is also an accurate, reliable tool for detecting ≥20–30% steatosis, with a sensitivity and specificity of 84.8% and 93.6%, respectively [16].…”
Section: Methodsmentioning
confidence: 99%
“…This ratio is reported to be useful in diagnosing cases of ≥30% steatosis [14]. The USG criteria were the presence of liver brightness and posterior attenuation, with stronger echoes in the hepatic parenchyma in comparison to the renal parenchyma and vessel blurring [15]. USG is also an accurate, reliable tool for detecting ≥20–30% steatosis, with a sensitivity and specificity of 84.8% and 93.6%, respectively [16].…”
Section: Methodsmentioning
confidence: 99%
“…• Three views in transverse plane: hepatic veins at the confluence with the inferior vena cava, right portal vein, and right posterior portal vein • One view in sagittal plane: liver and kidney These views were selected based on their favorable performance in previous papers. 9,10 Importantly, each view is routinely obtained during clinical US exams of the liver.…”
Section: Us Protocolmentioning
confidence: 99%
“…4 Various liver US image features, including vessel obscuration, posterior beam attenuation, and elevated liver-kidney contrast ratio, have been associated with liver fat. 9,10 Accumulation of fat modifies backscattering properties of liver tissue, 11 making the liver brighter in comparison to neighboring tissues, such as the kidney. 12,13 In addition, blood vessels within the liver become blurred or obscured as liver fat increases due to signal attenuation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that less portal venous blood flow and/or regional dilution of portal venous blood owing to anatomical variations of supplying vessels are present, therefore providing regional hepatocytes with less fatty substrates than the remaining parenchyma. In liver areas with reduced focal fat accumulation, fibrous tissue remodeling may occur, which seems to be caused by a different vascular supply compared with the rest of the liver [34,43,44,45,46,47,48,49,50,51]. However, the exact cause is unknown.…”
Section: Focal Fatty Sparingmentioning
confidence: 99%